Factors Influencing the Severity and Progression of Respiratory Muscle Dysfunction in Myotonic Dystrophy Type 1 - Hartog, Leigh; Zhao, Jing; Reynolds, Jerry; Brokamp, Gabrielle; Vilson, Ferdinand; Arnold, W. David; LoRusso, Samantha (Frontiers in Neurology, 2021)
Respiratory complications are the most common cause of death among patients with Myotonic Dystrophy type 1 (DM1), but the natural history of respiratory decline in DM1 patients is incompletely characterized and few predictors of the progression of respiratory dysfunction have been identified. To identify factors influencing the progression of respiratory dysfunction electronic medical records from 110 adult patients diagnosed with DM1 were reviewed along with data for respiratory symptoms and pulmonary function obtained from routine respiratory therapist clinical evaluations. At baseline, 70.9% had evidence of restrictive respiratory impairment. We examined various parameters of respiratory functional status, and found FVC (% predicted) correlated best with other measures of disease severity. Annual change in FVC was -1.42 (std error= 0.381). Greater CTG repeat size, higher MIRS rating, and longer disease duration were all correlated with lower baseline FVC but not with annual rate of change. Wide variability in clinical phenotype made determination of disease measures directly related to respiratory functional decline challenging.